2011
DOI: 10.1016/j.breast.2011.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Management of breast cancer with nanoparticle albumin-bound (nab)-paclitaxel combination regimens: A clinical review

Abstract: Although results of this review indicate that nab-paclitaxel may be an appropriate substitute for SBTs in combination regimens, additional research is required to confirm the place and cost effectiveness of these combinations before nab-paclitaxel could be recommended routinely in all settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…A previous global phase III study observed that weekly administration of nab-paclitaxel plus carboplatin yielded a significantly higher overall response rate compared with solvent-based paclitaxel plus carboplatin in patients with non-small cell lung cancer (NSCLC) (8). Nab-paclitaxel, a 130-nm albumin-bound paclitaxel formulation, is a promising novel agent for the treatment of NSCLC, and breast and gastric cancer (9,10). A previous preclinical study reported that nab-paclitaxel exhibited greater antitumor activity than equitoxic doses of Cremophor-based paclitaxel in xenograft models of lung (H522), breast (MX-1), ovarian (SK-OV-3), prostate (PC-3) and colon (HT29) human tumors (11).…”
Section: Discussionmentioning
confidence: 99%
“…A previous global phase III study observed that weekly administration of nab-paclitaxel plus carboplatin yielded a significantly higher overall response rate compared with solvent-based paclitaxel plus carboplatin in patients with non-small cell lung cancer (NSCLC) (8). Nab-paclitaxel, a 130-nm albumin-bound paclitaxel formulation, is a promising novel agent for the treatment of NSCLC, and breast and gastric cancer (9,10). A previous preclinical study reported that nab-paclitaxel exhibited greater antitumor activity than equitoxic doses of Cremophor-based paclitaxel in xenograft models of lung (H522), breast (MX-1), ovarian (SK-OV-3), prostate (PC-3) and colon (HT29) human tumors (11).…”
Section: Discussionmentioning
confidence: 99%
“…Many other Phase II neoadjuvant studies evaluating regimens including nab-PTX among HER2-negative patients have shown a wide range of pCR rates, from 7% to 25% (17)(18)(19) C, 500 mg/m 2 Day 1) in locally advanced breast cancer and reported a pCR rate of 17% in HER2-negative patients. We considered several reasons for the disappointingly low rate of pCR in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations have displayed a favorable pCR rate of 20-50% in HER2-negative patients who received qw nab-PTX in combination with carboplatin and bevacizumab in a neoadjuvant setting (17,23,24). Thus, the majority of neoadjuvant studies with nab-PTX have demonstrated satisfactory efficacy in combination regimes, but have not compared it with solvent-based taxanes (19). On the other hand, the radiological response after initiation of nab-PTX monotherapy in the current study demonstrated an acceptably high ORR of 71%, comparable to that of 60-70% reported in previous neoadjuvant studies on docetaxel and anthracycline (25)(26)(27) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…paclitaxel, and exhibit greater neurologic and hematologic toxicity. [47, 48] However, improving tumor specific targeting, optimizing the size and shape of nanoparticle and optimizing the tumor specificity of the gatekeeper may overcome these obstacles. [49, 50] Further, by exploiting tumor surface-specific features, an active targeting strategy can be developed which in turn enables the specific targeting of malignant cells.…”
Section: Inroductionmentioning
confidence: 99%